Effects of Teenage Pregnancy on Girl Child Education in Buhunga Sub-County Uganda. - Twikirize, Edwig (Kabale University, 2025)
Education is a global concern that closes the gap between social classes for safer communities. Promoting girl child education is possible once the schools embrace leadership styles for the same. School leaders facilitate the teachers, the students, and the community to embrace a hospitable, empathetic, and collaborative learning environment for the different students irrespective of their diversity. This study investigated the effects of teenage pregnancy on Girl Child Education in the Buhunga Sub-County of Rukungiri District in Uganda. The objectives were to find out the causes of Teenage Pregnancy in Buhunga Sub-County; to find out the psychosocial effects of teenage pregnancy on Girl Child academic performance in Buhunga Sub-County; to establish the health effects of teenage pregnancy on Girl Child Schooling in Buhunga Sub-County, and to suggest possible strategies for addressing teenage pregnancy in the Buhunga Sub-County of Rukungiri District. This study was based on a mixed-method design with a descriptive survey approach incorporated. The target population was 120 primary school teachers; 5 medical nurses; 10 religious leaders; 3 doctors; 30 VHTs; 01 CDO; the individuals; 01 L.C.III; 02 L.C. IIs; 01 Parish Chief; 04 LCIs; 03 CWC; 05 CYC. This study used purposive and simple random sampling to select 92 primary school teachers; 5 medical nurses; 10 religious leaders; 3 doctors; 28 VHTs; 01 CDO; the individuals; 01 L.C.III; 02 L.C. IIs; 01 Parish Chief; 04 LCIs; 03 CWC; 05 CYC. Data collection instruments were structured questionnaires and interviews to collect data on the effects of teenage pregnancy on Girl Child Education in Buhunga Sub-County of Rukungiri District, Uganda. Both qualitative and quantitative data were collected. Research ethical procedures were adhered to during the research process. Data analysis was adopted as quantitative analysis with the use of frequencies and percentages while qualitative analysis was adopted as thematic analysis. The study findings showed that the majority of the participants 80% strongly agreed that poverty made teenagers prone to being victims of early pregnancies before the right time; 83% strongly agreed that teenage peer social influence contributed to teenage pregnancies; 72% strongly agreed that parental neglect contributed to teenage pregnancies; 71% strongly agreed that family pressure for marriage contributed to teenage pregnancies. The psychosocial effects of teenage pregnancy on girl-child academic performance had teenagers living lifestyles associated with depression due to early pregnancies; socially segregated from the rest of the community members and school dropout due to early pregnancies. The health effects of teenage pregnancy on Girl Child schooling showed that teenagers’ pregnancy-related health issues limited teenagers’ school participation. The possible strategies for addressing teenage pregnancy for Girl Child Education were adopting teenage education about sexuality, promoting guidance and counseling in adolescents, abstinence education and awareness, promote gender equality campaigns. Conclusively, teenage pregnancy is escalated by poverty among teenagers, peer social influence in own curiosity experiences, parental neglect to avail guidance and counseling, lacking sex education, and family pressure for marriage to obtain resources. Psychosocially teenagers lived lifestyles associated with depression, experienced social segregation in their communities, suffered domestic violence consequences, lived in low-income life situations indulged teenagers in sexual intercourse at an early age. The health effects had teenagers limited further resilience to education. Adopting teenage education about sex education, preventing early marriages, teachers and guardians monitoring, promoting guidance and counseling in adolescents, and promoting gender equality campaigns for equality.